Advocacy in Translanguaging Education - Edina Krompák; Stephan Meyer; Elena Makarova (Multilingual Matters, 2026)
Vigorously advocates for realising translanguaging's transformative potential in education. This book examines diverse aspects of advocacy for translanguaging as a legitimate educational practice. It advances a practical theory of the translanguaging of education that is informed by deliberative advocacy and based in evidence. Combinations of quantitative and qualitative research from preschool to higher and adult education in different parts of the world give insight into current translanguaging strategies and pedagogies. From translanguaging and transsemiotising in subject lessons such as Mathematics and Geography, to transdisciplinary engagement with poetry and music beyond the classroom, the findings contribute to the development of a practical theory of translanguaging in education, and demonstrate how translanguaging plays a part in everyday language learning and language use. This book is open access under a CC BY ND licence.